2021
DOI: 10.3390/curroncol28060414
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of CRC Stage at Diagnosis among Male and Female Adults Participating in a Prospective Cohort Study: Findings from Alberta’s Tomorrow Project

Abstract: Colorectal cancer (CRC) is a leading cause of morbidity and mortality in Canada. CRC screening and other factors associated with early-stage disease can improve CRC treatment efficacy and survival. This study examined factors associated with CRC stage at diagnosis among male and female adults using data from a large prospective cohort study in Alberta, Canada. Baseline data were obtained from healthy adults aged 35–69 years participating in Alberta’s Tomorrow Project. Factors associated with CRC stage at diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 103 publications
1
13
0
Order By: Relevance
“…Gender. In some Western countries, the CRC incidence does not differ between female and male patients (Abotchie, Vernon, & Du, 2012; Ghebrial et al, 2021). The current study showed slight predominance of female patients, who constituted 53.4 % (95 % CI 49.2-57.5 %) of the study group.…”
Section: Clinical and Morphological Findingssupporting
confidence: 44%
“…Gender. In some Western countries, the CRC incidence does not differ between female and male patients (Abotchie, Vernon, & Du, 2012; Ghebrial et al, 2021). The current study showed slight predominance of female patients, who constituted 53.4 % (95 % CI 49.2-57.5 %) of the study group.…”
Section: Clinical and Morphological Findingssupporting
confidence: 44%
“…After univariate analysis, the results of the research were carried out using bivariate analysis, namely by using the chi-square test, the relationship between the independent variables and the dependent variable with the significance limit of the p-value statistical calculation (0.05) [6], the following results were obtained:…”
Section: Resultsmentioning
confidence: 99%
“…Apart from treatments once cancer occurs, it is important to recognize the disease as soon as possible to increase the chances of recovery [5][6][7][8]. One reason why lung cancer is the deadliest cancer type is that it is difficult to detect in early stages and hard to cure in an advanced stage [9,10].…”
Section: Introductionmentioning
confidence: 99%